The Democratic Intellect - Davie, George (Edinburgh classic editions, 2013)
George Davie's revolutionary account of the intellectual movements which set Scotland apart from its neighbours. First published in 1961, it proved seminal in restoring Scotland's appreciation of the value of its cultural identity. Here reissued as an Edinburgh Classic edition to coincide Scotland Independence debate of 2014.